Discipline and Leadership Organizational Communication and Principal Conflict Management in MTsN 1 Luwu - M. Saing; Sukirman Nurdjan; Baso Hasyim (International Journal of Educational Administration, Management, and Leadership, 2024)
This study aims to analyze the role of organizational communication and conflict management strategies used by the principal to improve the discipline of educators and staff at MTsN 1 Luwu. Using a descriptive qualitative approach and case study design, data were gathered through in-depth interviews, field observations, and document analysis. The results show that the principal uses open and thorough communication via various formal and informal channels to foster harmonious working relationships. Conflict management strategies include participatory approaches, mediation, and dialogue-based resolution, which effectively reduce misunderstandings and promote compliance with institutional rules. The principal’s motivation for managing communication and conflict stems from the desire to create a supportive and professional work environment focused on improving educational quality. These findings suggest that effective communication and conflict management directly and positively influence the discipline level among teachers and staff. The study recommends enhancing school leadership skills in interpersonal communication and conflict resolution as key strategies for educational management.